PENGARUH WORKING CAPITAL, FIXED FINANCIAL ASSETS, FINANCIAL DEBT , DAN FIRM SIZE TERHADAP PROFITABILITAS - Farah Margaretha; Nina Adriani (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2008)
The purpose of this research is to analyze the influence of working capital, fixed financial assets, financial debt and firm size on probability. Data of this research is obtained from 19 companies of textile and garment industry that have been listed on Jakarta Stock Exchange and it has selected using purposive sampling method during 2001 to 2005. Data analysis method used in this research are multiple linier regression and testing hypothesis. Independent variables used in this research are working capital, fixed financial assets, financial debt and firm size and the dependent variable is profitability. Based on testing hypothesis, we have results that working capital and firm size have positive effect and significant on profitability whereas fixed financial assets and financial debt have negative effect and significant on profitability. The implication of this research explain that the company need to play attention on working capital management, fixed financial assets, sales and debt proportion because all those things have influence on profitability.